ANALISIS PERFORMANCE TURBINE PROPELLER DENGAN MENGGUNAKAN METODE CFD (COMPUTATIONAL FLUID DYNAMIC) - Widodo, Aditya Putra; Subekti, Subekti (Universitas Mercu Buana, 2023)
Wind power plants that are developing at this time still have relatively little power, this is because the existing turbines still have low efficiency. Therefore, in this final project a propeller turbine blade which was originally with a flat blade will be developed by adding variations in the number of blades and adding winglets to the blade tip. This study aims to simulate the CFD to determine the relationship of wind flow velocity, winglet on the blade and the effect of the number of blades on the performance of the turbine and compare the results of the simulation with the results of trials on the wind tunnel.The analysis process uses the CFD method using ANSYS CFX 15.0. n this case the researchers made a turbine with 3 variations, namely: 3 blade variation, 4 blade variation and 5 blade variation. Giving variations in the number of blades affect the performance of the turbine. From these three variations, this study obtained the greatest power of 4.0794 watts on a variation of 5 blades as evidenced by an increase in graph trends in the amount of power vs. the number of blades from variation 1, variation 2 and variation 3 with the same rpm is 636 rpm. From the results of the best design then made a prototype then carried out trials on the wind tunnel in the UMB Mechanical Engineering laboratory. Subsequent trial results will be compared with simulation results based on the same speed and rpm parameters.The research that has been carried out gets greater simulation results compared to the power of the trial results, but the results of the simulation and trials have the same trend that the higher the wind speed, the greater the power generated by the turbine. The simulation results produce the greatest power of 4.001 watts with wind speed of 5.0m / s and a rotating speed of 627 rpm while experiment have power about 1,224 watts with a wind speed of 5.0m / s and a rotating speed of 627 rpm